The The Effectiveness of Experiential-Learning–Based Group Counseling Embedded with Ca’oca’an to Enhance Madurese Students’ Emotional Intelligence - M. Ismail Makki; Aflahah; Khairul Bariyah; Hasrul (G-Couns: Jurnal Bimbingan dan Konseling, 2026)
This study examines the effectiveness of experiential learning–based group counselling, embedded with Ca’oca’an, in enhancing Madurese students’ emotional intelligence. Emotional intelligence follows Goleman’s five dimensions: self-awareness, self-regulation, self-motivation, empathy, and social skills. An experimental equivalent time-series design was used with 12 students at Madrasah Aliyah Mabdaul Falah Pamekasan. The intervention comprised two cycles of group counseling that integrated Ca’oca’an proverbs into the four stages of experiential learning. Emotional intelligence was measured with a Likert-type scale at pretest, posttest 1, and posttest 2. Wilcoxon signed-rank tests and normalized gain scores showed significant improvements at each measurement point, with an overall N-gain of 0.87 (high). The largest gains were in self-awareness and self-regulation, supported by qualitative reflections showing better emotional awareness, self-control, empathy, and interpersonal behavior. These findings indicate that experiential-learning–based group counseling grounded in local wisdom is effective and culturally responsive for strengthening students’ emotional intelligence. Keywords: emotional intelligence, experiential learning, group counselling, Ca’oca’an, local wisdom